BIT ERROR OPTIMIZATION OF CODED OFDM SYSTEM OVER RAYLEIGH FADING CHANNEL - Awatif Ali Jafaar; Zainab Majeed Abid (Journal of Engineering and Sustainable Development, 2019)
Low-Density Parity-Check (LDPC) codes are one of the hottest topics in coding theory today. This code was invented in the early 1960s, and it having an amazing comeback in the last few years. In this paper, a scheme is proposed to analyze the performance of LDPC which is considered an important rival to turbo codes, Convolutional Code (CC), and Read Solomon (RS) in terms of performance and complexity. This code is utilized in the Orthogonal Frequency Division Multiplexing (OFDM) system to evaluate the improvement in the Bit Error Rate (BER) performance of the system. Comparison is done between turbo code and LDPC code through Additive White Gaussian Noise (AWGN) and fading channels. The effect of varying the code rate channel, number of iterations, and code length on the performance of the scheme is also explained.